Salt tea consumption and esophageal cancer: A possible role of alkaline beverages in esophageal carcinogenesis. Issue 6 (6th October 2014) - Dar, Nazir Ahmad; Bhat, Gulzar Ahmad; Shah, Idrees Ayoub; Iqbal, Beenish; Rafiq, Rumaisa; Nabi, Sumaiya; Lone, Mohd Maqbool; Islami, Farhad; Boffetta, Paolo
<x xml:space="preserve">Abstract</x> Salt tea is the most commonly used beverage in Kashmir, India, where esophageal squamous cell carcinoma (ESCC) is the most common cancer. Salt tea is brewed in a unique way in Kashmir, usually with addition of sodium bicarbonate, which makes salt tea alkaline. As little information about the association between salt tea drinking and ESCC was available, we conducted a large‐scale case‐control study to investigate this association in Kashmir. We recruited 703 histologically confirmed cases of ESCC and 1664 controls individually matched to cases for age, sex, and district of residence. Conditional logistic regression models were used to calculate odds ratios (ORs) and 95% confidence intervals (95% CIs). Participants who consumed >1, 250 ml day−1 showed an increased risk of ESCC (OR = 2.60, 95% CIs = 1.68–4.02). Samovar (a special vessel for the beverage preparation) users (OR = 1.77, 95% CIs 1.25–2.50) and those who ate cereal paste with salt tea (OR = 2.14, 95% CIs = 1.55–2.94) or added bicarbonate sodium to salt tea (OR = 2.12, 95% CIs = 1.33–3.39) were at higher risk of ESCC than others. When analysis was limited to alkaline tea drinkers only, those who both consumed cereal paste with salt tea and used samovar vessel were at the highest risk (OR = 4.58, 95% CIs = 2.04–10.28). This study shows significant associations of salt tea drinking and some related habits with ESCC risk.